Gas turbine generating units control via feedback linearization approach. (15th February 2017) - Bonfiglio, A.; Cacciacarne, S.; Invernizzi, M.; Procopio, R.; Schiano, S.; Torre, I.
Abstract: The aim of the present paper is that of proposing an innovative control strategy based on the FeedBack Linearization (FBL) technique in order to achieve a high performance and decupled control of a gas generating unit. The dynamic performances of a gas generating units are limited by the combustion chamber dynamics where sudden temperature variation may lead to undesired and dangerous phenomena. The FBL application will allow introducing an ideal decupling of the regulated channels so that power variation will have a minimal impact on the combustion chamber temperature obtaining a smoother and quicker response to reference changes in comparison with a tradition, PID based control. The proposed FBL controller will be also tested in presence of model and parameters uncertainties in order to verify the robustness of the proposed control technique. Highlights: Feedback linearization control for gas generating units. Decoupled power and temperature control. Gas generating units modeling and control. Validation simulation and sensitivity analysis.